The Role of the Available Potential Energy in the Atmosphere - Camerlengo, Alejandro Livio; Saadon, Mohd Nasir (Universiti Putra Malaysia Press, 1999)
A major problem in atmospheric energetic dynamics is addressed. In using a particular mathematical derivation it is verified that 0.5% of the total potential energy is available for conversion into kinetic energy.